2009
DOI: 10.1097/scs.0b013e3181bec611
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Reconstruction of the Jaw With Fibular Grafts and Implants

Abstract: Reconstructive treatments for jaw defects are complex procedures that can combine multiple techniques including fibula free flap (FFF) grafting. The purpose of this retrospective study was to document and share our experience on mandibular and maxillar reconstruction with FFF followed by secondary dental rehabilitation using implant insertion.We reviewed 198 patients treated by FFF grafting for mandibular and/or maxillary defects in our department during the past 11 years (1996-2007). A selection of 30 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 27 publications
1
71
0
1
Order By: Relevance
“…Various reviews have shown that only about 15-25 % of patients who have been reconstructed end up with dental rehabilitation, the remainder of patients staying functionally crippled [5,6]. One of the causes for such a low rate of rehabilitation is that the reconstructed bone is in a poor relation to support implants.…”
Section: Discussionmentioning
confidence: 99%
“…Various reviews have shown that only about 15-25 % of patients who have been reconstructed end up with dental rehabilitation, the remainder of patients staying functionally crippled [5,6]. One of the causes for such a low rate of rehabilitation is that the reconstructed bone is in a poor relation to support implants.…”
Section: Discussionmentioning
confidence: 99%
“…Les techniques actuelles de réparation privilégient l'apport de tissu osseux autologue, sous forme de greffes osseuses non vascularisées [1,2] ou de lambeaux libres micro-anastomosés [3], car l'utilisation de ces greffons autologues permet de réduire les phénomènes de rejet immunitaire. Ces techniques permettent ainsi l'apport conjoint d'un support (ou matrice) et de cellules osseuses, fonctionnelles et actives, ainsi qu'une éventuelle suppléance vasculaire en fonction de la technique chirurgicale et du volume greffé.…”
Section: Résuméunclassified
“…However, Raoul et al suggested that implant placement should be avoided in areas that have received radiotherapy doses of more than 50 Gy (Raoul et al, 2009 Raoul et al reported that implant loss occurred only in 1 irradiated vascularized fibula flap among a total of 18 implants placed in 6 patients, representing a success rate of 94% (Raoul et al, 2009). Salinas et al reported a 72.5% osseointegration rate for 51 implants placed in 22 patients (Salinas et al, 2010).…”
Section: Dental Implantsmentioning
confidence: 99%